The Evolution of Thematic and Integrative Approaches in Social Studies Education: A Historical and Conceptual Analysis - Eka Yuliana Rahman; Nana Supriatna; Juju Masunah; Erlina Wiyanarti; Nur Allan Lasido; Moh Fikri Pomalingo (IAIN Manado, 2025)
This article examines thematic and integrated approaches in Social Studies Education through ontological, epistemological, and axiological perspectives. It arises from the limited availability of studies that explore these approaches from historical and developmental perspectives. The purpose of this literature research is to describe the early evolution of thematic and integrated approaches and to explain how educational practices have changed over time. Using the library research method by Both and Williams (2016), the study follows ten stages of data collection, analysis, and reduction based on relevant references. Through the Publish or Perish application, 30 relevant articles were identified using the keywords